Genetic algorithms for VLSI micro-Cell layout area optimization based on binary tree - Hasliza, A. Rahim@Samsuddin; Ab Al-Hadi, Ab Rahman; R. Badlishah, Ahmad; 'Aini Syuhada, Md Zain; M.I., Ahmad; Wan Nur Suryani Firuz, Wan Arrifin (ACTA Press, 2009)
Link to publisher's homepage at http://www.actapress.com